How to manage dementia in general practice - Clarke, Nicholas, 1961-; Clarke, Farine; Edwards, Denzil, 1954- (Chichester, West Sussex, UK : Wiley-Blackwell/BMJ Books, 2013)
This guide clearly shows each stage in the management of a patient with dementia. It covers the complex issues surrounding dementia such as spouses and families, access to appropriate care, legal and ethical concerns, planning for the future and "living well" and includes the decision making process on initiating treatment and guidance on how best to access the available services.
Diagnosing dementia in general practice -- Complex pictures of dementia -- Initiating, monitoring, and adjusting dementia treatments -- Emergency management of dementia -- Managing families -- Using the multidisciplinary team -- Capacity, consent, and deprivation of liberty -- Choosing a residential home -- Research, developments, and media coverage -- GP questions answered.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Dementia -- Diagnosis; Dementia -- Treatment; Dementia -- diagnosis; Dementia -- therapy; Early Diagnosis; General Practice; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Dementia -- Diagnosis; Dementia -- Treatment; Electronic books